Changes in subjective mental and physical fatigue during netball games in elite development athletes. Issue 6 (June 2020) - Russell, Suzanna; Jenkins, David; Halson, Shona; Kelly, Vincent
Abstract: Objectives: To assess the magnitude of changes in, and relationships between, physical and mental fatigue pre-to-post match in elite development netballers. Design: Observational. Methods: Twelve female netballers (21.3 ± 2.9 years) competing in the Australian Netball League reported perceptual measures of mental and physical fatigue pre- and post-match on 12 separate competition occasions. Minutes played, to allow for calculation of weighted changes (ratings proportional to playing time), positional groups and performance analysis variables were also assessed. Results: Post-match ratings were higher (p < 0.01) than pre-match for both mental (pre: 31.02 ± 19.28; post: 44.73 ± 24.47) and physical fatigue (pre: 28.86 ± 15.37; post: 47.21 ± 24.67). The correlation coefficient between change in mental and physical fatigue (r = 0.37, p < 0.01) revealed a shared variance of 13.9%. Acute changes in mental fatigue were related to minutes played (r = 0.32, p < 0.01) as was change in physical fatigue (r = 0.59, p < 0.01). No differences in change in mental fatigue were found between positional groups (p = 0.07) though change in physical fatigue was higher for shooters compared to defenders (p < 0.05). Performance variables revealed no relationships with mental or physical fatigue, with the exception of turnover number with both post-match weighted physical (r= -0.23, p < 0.01) and weighted-change in physical fatigue (r = −0.16, p < 0.05). Conclusions: Mental and physical fatigue were found to increase across netball matches in elite development athletes. Mental fatigue emerged as a largely separate construct to physical fatigue.